2017
DOI: 10.3389/fphys.2017.00231
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Mutations in Grade II and III Glioma Cell Lines Are Associated with Significant Mitochondrial Dysfunction and Higher Oxidative Stress

Abstract: The role of mitochondria in tumorigenesis has regained much attention as it could dysregulate cellular energetics, oxidative stress and apoptosis. However, the role of mitochondria in different grade gliomasis still unknown. This study aimed to identify mitochondrial DNA (mtDNA) sequence variations that could possibly affect the mitochondrial functions and also the oxidative stress status. Three different grades of human glioma cell lines and a normal human astrocyte cell line were cultured in-vitro and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
(87 reference statements)
1
12
0
Order By: Relevance
“…A recent work by Soon et al reported that mitochondrial DNA is mutated in several glioma cells and could subsequently induce mitochondrial dysfunction and higher oxidative stress (53). Mitochondrion dysfunction has been theorized as a crucial player in many tumors by increasing the production of reactive oxygen species (ROS) through the activity of the mitochondrial electron transport chain (54).…”
Section: Discussionmentioning
confidence: 99%
“…A recent work by Soon et al reported that mitochondrial DNA is mutated in several glioma cells and could subsequently induce mitochondrial dysfunction and higher oxidative stress (53). Mitochondrion dysfunction has been theorized as a crucial player in many tumors by increasing the production of reactive oxygen species (ROS) through the activity of the mitochondrial electron transport chain (54).…”
Section: Discussionmentioning
confidence: 99%
“…Obtusifolin protects cells against high glucose-induced apoptosis. Mitochondrial dysfunction could activate mitochondria-dependent apoptosis pathway (22). The flow cytometry analysis showed that cell apoptosis caused by hyperglycemia was significantly inhibited in the obtusifolin pretreatment groups (Fig.…”
Section: Obtusifolin Protects Huvecs From Oxidative Stressmentioning
confidence: 93%
“…The issues with the analysis of nucleic acids in peripheral blood are similar with the problems encountered when searching for high-molecular polar central nervous system (CNS)-derived compounds. In particular, low concentration, low abundance of the compounds in the systemic circulation, coupled with their weak penetration thought the BBB, make brain tumor-derived nucleic acids difficult to be identified as circulating molecules [31,119,120,121,122,123,124].…”
Section: Perspective Biomarkersmentioning
confidence: 99%